Potential CD34 signaling through phosphorylated-BAD in chemotherapy-resistant acute myeloid leukemia. (4th May 2019) - Yiau, Stephnie Kang-Xian; Lee, CinDee; Mohd. Tohit, Eusni Rahayu; Chang, Kian Meng; Abdullah, Maha
Abstract: Acute myeloid leukemia (AML) constitutively express growth factors and cytokines for survival. Chemotherapy alters these signals to induce cell death. However, drug resistance in AML remains a major hindrance to successful treatment and early warning is unavailable. Modulation of signaling pathways during chemotherapy may provide a window to detect response and predict treatment outcome. Blood samples collected from AML patients before and at day-3 of induction therapy were compared for changes in expression of CD117, CD34, pro-inflammatory cytokines and mediators of Akt and MAPK pathways, using multi-color flow cytometry. Nine patients were diagnosed as drug-resistant and seven sensitive to chemotherapy. Twelve were paired. Average percentages of CD34 (66.8 ± 11.7% vs. 26.2 ± 5.8%, p  = 0.033) and pBAD (66.9 ± 8.2% vs. 28.9 ± 8.2%, p = 0.016) were significantly increased in chemo-resistant ( N  = 9) compared to chemo-sensitive ( N  = 5) samples. Percentages of CD34 were strongly correlated with pBAD ( R  = 0.785; p  = 0.001; N  = 14) and pFKHR ( R  = 0.755; p  = 0.002; N  = 14) at day-3 induction. Chemo-sensitive cases expressed significantly higher percentages of IL-18Rα (71.9 ± 9.6% vs. 29.8 ± 5.8%, p  = 0.016). Though not significantly different in the outcome, IL-1β was strongly associated with activated Akt-S473, IL-6 with phosphorylated JNK and FKHR while TNF-α appeared to trigger Bim, in treated samples. These preliminary results suggested AML cells resistant to chemotherapy increased expression of CD34 and may signal through pBAD while cells sensitive to chemotherapy-induced IL18Rα expression. These were observed early during induction therapy. Identifying CD34 is interesting as it is a convenient marker to monitor drug-resistance in AML patients. Inhibition of CD34 and pBAD signaling may be important in treating drug-resistant AML.